Existence of Outdoor Reklame Assessed from The Estethics of The Public Space in Teuku Umar Denpasar - Adistanaya, I Gusti Bagus (Journal of A Sustainable Global South; Vol 4 No 2 (2020): August 2020, 2020)
The rise of trade and service competition affects the emergence of various promotional media whose existence is placed in strategic spaces in urban centers that cause discomfort and decreased quality of the beauty of the city. This study aims to examine the typology of outdoor signage, public perception of the existence of outdoor signage and its influence on the aesthetics of public space. Data collection is done through a qualitative (descriptive) approach. Descriptive qualitative analysis techniques are used to describe and explain certain phenomena using descriptions, explanations and understandings. In this research activity, descriptive qualitative analysis techniques are used to explain the general picture and the results of interviews so that the analysis conducted must be able to produce output in accordance with the goals and objectives set. The results of the analysis show that the advertisement characteristics in the public spaces of Teuku Umar Denpasar street are dominated by commercial outdoor signage. Respondents' perceptions of the existence of outdoor billboards showed (66%) assessed that billboards had not created city order, (60%) assessed that they had not created city beauty, (80%) rated size as inappropriate, (74%) assessed attractive colors, (77%) rate disturbing lighting and (86%) rate disturbing the building facade as big as. From the results of the analysis, regulations are needed to bring order to reinstall outdoor billboards in order to create order and beauty of the city of Denpasar. Index Terms — outdoor billboards, aesthetics, public space